Viscoelastic monitoring in trauma resuscitation. (22nd October 2020) - Sayce, Andrew C.; Neal, Matthew D.; Leeper, Christine M.
Abstract: Background: Traumatic injury results in both physical and physiologic insult. Successful care of the trauma patient depends upon timely correction of both physical and biochemical injury. Trauma‐induced coagulopathy is a derangement of hemostasis and thrombosis that develops rapidly and can be fatal if not corrected. Viscoelastic monitoring (VEM) assays have been developed to provide rapid, accurate, and relatively comprehensive depictions of an individual's coagulation profile. VEM are increasingly being integrated into trauma resuscitation guidelines to provide dynamic and individualized guidance to correct coagulopathy. Study Design and Methods: We performed a narrative review of the search terms viscoelastic, thromboelastography, thromboelastometry, TEG, ROTEM, trauma, injury, resuscitation, and coagulopathy using PubMed. Particular focus was directed to articles describing algorithms for management of traumatic coagulopathy based on VEM assay parameters. Results: Our search identified 16 papers with VEM‐guided resuscitation strategies in adult patients based on TEG, 12 such protocols in adults based on ROTEM, 1 protocol for children based on TEG, and 2 protocols for children based on ROTEM. Conclusions: This review presents evidence to support VEM use to detect traumatic coagulopathy, discusses the role of VEM in trauma resuscitation, provides a summary of proposed treatment algorithms, and discusses pending questions in the field.